A fluorescent probe for Cd2+ detection based on the aggregation-induced emission enhancement of aqueous Zn–Ag–In–S quantum dots. Issue 19 (29th April 2019) - Wei, Chang; Wei, Xian; Hu, Zhe; Yang, Dan; Mei, Shiliang; Zhang, Guilin; Su, Danlu; Zhang, Wanlu; Guo, Ruiqian
Abstract : A sensitive and selective fluorescent probe for the cadmium ion (Cd 2+ ) was developed based on the aggregation-induced emission enhancement (AIEE) of Zn–Ag–In–S quantum dots (ZAIS QDs). Abstract : A sensitive and selective fluorescent probe for the cadmium ion (Cd 2+ ) was developed based on the aggregation-induced emission enhancement (AIEE) of Zn–Ag–In–S quantum dots (ZAIS QDs). The QDs were synthesized by a convenient hydrothermal method withl -cysteine as ligands, with the average size of 3.2 nm and the emission peak at 520 nm. The interference study indicated the good selectivity of the probe. It has a broad detection range from 25 μM to 2 mM and the detection limit is 1.56 μM. AIEE is triggered by the interaction between Cd 2+ and thiol groups on the surface of QDs, which causes weaker electrostatic repulsion between QDs and the passivation of surface defects. To the best of our knowledge, this is the first report on the AIEE of quaternary QDs. The method was successfully applied to the determination of Cd 2+ in water samples with recoveries between 98.1% and 103.3%. This work shows its potential as a candidate for Cd 2+ detection and provides a new understanding of AIEE.